THE THE ANALYSIS OF STUDENTS’ ABILITY IN APPLYING MODULATION TECHNIQUE IN TRANSLATING COLLOCATION ON “THE LOST SYMBOL” NOVEL BY DAN BROWN: (A Descriptive Study at 6th Semester Students’ of PBI IAIN Bengkulu in The Academic Year of 2019). - Detty Lis Mayanti (Edu-Ling: Journal of English Education and Linguistics, 2019)
The objective of this research was to analyze how students’ ability in applying modulation technique in translating collocation from the novel “The lost Symbol” by Dan Brown. The research was a content analysis of descriptive qualitative. The population was the 6thsemester students of PBI IAIN Bengkulu in academic year 2019 with a total number of students 120 students. Out of this population, 25 students were taken as respondent, there were refresented from each class. The data were collected by using translation test which was contained six types of collocation. The data was found that the result of students’ average score in collocation that researched as follow: Adjective and noun ware 60% (average) ,Noun and noun were 49% (very poor), Noun and verb were 41.6% (very poor), Verb and expression with preposition were 22,88% (very poor). The finding showed that there that the students’ability is dominant in collocation type of adjective and noun because to translate it just simple and the phrase of word is most familiar in their activities not also in translation subject but other skill language material. In other hand, the students’ low ability in translate collocation of Verb and expression with prepositionbecause they could not just use the literal translation but they have to adapt it or changenged their point of view and use their cognitive and focus on the context, which make relevant and coherent.However, overall the average of students ability must be improved it with learn more and lecturer must be able to focus on students’ weakness in applying translation technique especially on modulation to get the progress by the students’ translation well.